Full-disc 13CO(1-0) mapping across nearby galaxies of the EMPIRE survey and the CO-to-H2 conversion factor - Cormier, Diane; Bigiel, Frank; Jiménez-Donaire, Maria Jesús (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. Carbon monoxide (CO) provides crucial information about the molecular gas properties of galaxies. While 12CO has been targeted extensively, isotopolo